Analysis of Free Morphemes and Bound Morphemes in the Lyrics of the Song "Best Part" By Daniel Caesar and H.E.R - ., Ulfayanti; Putri Nuraura Alfiani; Ahmad Fauzi MZ; Harmilawati (Darussalam English Journal (DEJ), 2024)
This study analyzes free morphemes and bound morphemes in the lyrics of the song "Best Part" by Daniel Caesar and H.E.R. Using a literature review approach, the main data were taken from the official lyrics obtained from the Genius website, and secondary sources such as books and journals relevant to morphological theory and lyric analysis. The results show that the lyrics of "Best Part" contain various free morphemes, including nouns, verbs, adjectives, conjunctions, prepositions, articles, and pronouns. Additionally, bound morphemes in the form of suffixes were also found. These findings provide insights into how linguistic elements play a role in creating meaning and conveying messages through song lyrics.